Loss of HIF-1α in natural killer cells inhibits tumour growth by stimulating non-productive angiogenesis. Issue 1 (December 2017) - Krzywinska, Ewelina; Kantari-Mimoun, Chahrazade; Kerdiles, Yann; Sobecki, Michal; Isagawa, Takayuki; Gotthardt, Dagmar; Castells, Magali; Haubold, Johannes; Millien, Corinne; Viel, Thomas; Tavitian, Bertrand; Takeda, Norihiko; et al.
Abstract Productive angiogenesis, a prerequisite for tumour growth, depends on the balanced release of angiogenic and angiostatic factors by different cell types within hypoxic tumours. Natural killer (NK) cells kill cancer cells and infiltrate hypoxic tumour areas. Cellular adaptation to low oxygen is mediated by Hypoxia-inducible factors (HIFs). We found that deletion of HIF-1α in NK cells inhibited tumour growth despite impaired tumour cell killing. Tumours developing in these conditions were characterised by a high-density network of immature vessels, severe haemorrhage, increased hypoxia, and facilitated metastasis due to non-productive angiogenesis. Loss of HIF-1α in NK cells increased the bioavailability of the major angiogenic cytokine vascular endothelial growth factor (VEGF) by decreasing the infiltration of NK cells that express angiostatic soluble VEGFR-1. In summary, this identifies the hypoxic response in NK cells as an inhibitor of VEGF-driven angiogenesis, yet, this promotes tumour growth by allowing the formation of functionally improved vessels. Tumour hypoxia influences both the immune responses and angiogenesis. Here, the authors show that HIF-1α deletion in NK cells impairs NK cytotoxic activity but inhibit tumour growth by decreasing the infiltration of NK cells that express angiostatic soluble VEGFR-1, thus resulting in non-functional angiogenesis.